2021
DOI: 10.1177/13506501211002962
|View full text |Cite
|
Sign up to set email alerts
|

Influence of slip-flow phenomenon on thermohydrodynamic behaviour of gas foil thrust bearings

Abstract: Gas foil bearings are often used in high-speed turbomachinery such as turboexpanders and turbochargers due to their merits over simple gas-lubricated bearings. The merits of gas foil bearings include their ability to tailor dynamic parameters such as stiffness and damping. Gas foil bearings usually have low clearance and operate at a high rotational speed, which eventually leads to velocity slip at the solid–fluid interface. This article investigates the effect of slip flow on various parameters of gas foil th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…A separate numerical analysis was also conducted which shows forced convection in bump channels is an effective approach for better cooling at high loads. Much recently, Kumar et al 101 investigated the impact of slip flow phenomenon on THD behaviour of GFTB. The model includes the use of first-order slip velocity (equation ( 18)) at the solid-fluid interface and thus modifies Reynold's equation.…”
Section: Gftbmentioning
confidence: 99%
“…A separate numerical analysis was also conducted which shows forced convection in bump channels is an effective approach for better cooling at high loads. Much recently, Kumar et al 101 investigated the impact of slip flow phenomenon on THD behaviour of GFTB. The model includes the use of first-order slip velocity (equation ( 18)) at the solid-fluid interface and thus modifies Reynold's equation.…”
Section: Gftbmentioning
confidence: 99%
“…A negligible effect was observed in the parameters like torque and power loss due to the slip flow. Subsequently, Kumar et al [72] incorporated the slip-flow effect in in a GFTB model and presented a modified Reynolds equation with the first-order slip condition. It was observed that the traditional Reynolds equation has a bias towards overestimating the load-carrying capacity of the GFTB.…”
Section: Coupled Fluid-structure Modelmentioning
confidence: 99%
“…It was found that the thermal expansions of the rotor and bearing structure were the main cause of TEI. Kumar 23 established a model of helium gas lubricated thrust bearing and compared the difference in the gas foil thrust bearing thermal characteristics under slip and no-slip conditions by finite difference method. Liu 24 compared and analyzed the effects of the rotating speed, bearing load and cooling airflow on the thermal distribution of foil gas bearing through experiments and simulations.…”
Section: Introductionmentioning
confidence: 99%